PLAY THERAPY AND ITS EFFECT ON ANXIETY LEVELS IN HOSPITALIZED PEDIATRIC PATIENTS: A LITERATURE REVIEW - Wahyudi, Totok; Mustain, Mustain; Rahmasari, Ikrima; Nurmawati, Niya (LPPM Universitas Duta Bangsa Surakarta, 2025)
Hospitalization in children often leads to stress and anxiety due to separation from parents, unfamiliar environments, and invasive medical procedures. These conditions can negatively impact children’s emotional well-being and recovery. Play therapy has been identified as an effective non-pharmacological intervention to reduce anxiety and support coping mechanisms during hospitalization. This literature review was conducted through a comprehensive search of journal databases including ScienceDirect, PubMed, and Google Scholar, using the keywords Play therapy, Therapeutic play, Anxiety, Child, and Hospitalized. The inclusion criteria were full-text articles published within the last five years, including systematic reviews, randomized controlled trials, clinical trials, and meta-analyses. The reviewed studies consistently show that play therapy effectively reduces anxiety in hospitalized children. Interventions such as coloring, storytelling, role-playing with medical kits, puppet play, and traditional games like snakes and ladders were associated with lower anxiety scores, improved cooperation, and greater comfort during medical procedures. Moreover, parental involvement was highlighted as a crucial factor in optimizing therapeutic outcomes by providing emotional, psychological, and spiritual support to children. Play therapy serves as an effective complementary intervention to alleviate anxiety and enhance cooperation in hospitalized children. Integrating therapeutic play into pediatric care, combined with active parental involvement, not only improves the hospital experience but also promotes holistic child development and emotional resilience.